The combination of isomalto-oligosaccharides (IMO)-based dietary fiber and hypocaloric high-protein diet could improve the anthropometric profile and fasting plasma glucose of healthy adults: A repeated single-arm clinical trial - Hendy Wijaya; Yu Hirata; Lidya Handayani Tjan; Yudy Tjahjono; Kuncoro Foe; Caroline; Diga Albrian Setiadi; Hevi Wihadmadyatami; Bernadette Dian Novita; FX Himawan Haryanto Jong; Wilson Christianto Khudrati (Contemporary Clinical Trials Communications, 2022)
Background and aims: Meals with high protein and fiber could reduce weight and improve diabetes risk factors. Isomalto-oligosaccharide (IMO), a form of dietary fiber, could induce the afferent signal that causes appetite suppression. However, the direct effect of fiber supplementation in the form of IMO combined with a high-protein diet (HPF) on those parameters is still unknown. This study aims to investigate the effect of HPF on anthropometric parameters and blood glucose regulation of healthy subjects.   Methods: Thirteen healthy subjects were given a hypocaloric high protein diet (HPD) mixed with their prepared meals for two weeks. Followed by the HPF diet for another two weeks. Their anthropometric parameters, such as body composition (total body weight, body fat percentage, and fat-free mass), BMI and waist circumference, and fasting plasma glucose, were measured. Results: Compared to pre-intervention, HPF could significantly (p ≤ 0.004) reduce the anthropometric parameters and fasting plasma glucose. Compared to HPD, HPF could significantly (p ≤ 0.005) reduce more total body weight, body fat percentage, and BMI. In addition, HPF could induce more satiety than HPD (higher VAS score). Conclusion: HPF could improve the subject's anthropometric parameters which is obviously beneficial in preventing the risk of developing diabetes.